2014
DOI: 10.1021/om500311a
|View full text |Cite
|
Sign up to set email alerts
|

B–H Bond Cleavage via Metal–Ligand Cooperation by Dearomatized Ruthenium Pincer Complexes

Abstract: Organic derivatives of boronic acid are widely used reagents useful in various synthetic applications. A fundamental understanding and the exploration of new reaction pathways of boronic reagents with organometallic systems hold promise for useful advancement in chemical catalysis. Herein we present the reactions of simple boranes with dearomatized ruthenium pincer complexes based on PNP (2,6-bis(di-tert-butylphosphinomethyl)pyridine) or PNN (2-(di-tert-butylphosphinomethyl)-6-(diethylaminomethyl)pyridine) lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 105 publications
0
44
0
4
Order By: Relevance
“…Upon reaction of the dearomatized ruthenium pincer complex 27 (scheme 12) with pinacolor catechol borane, facile B-H bond cleavage occurred [31]. Unexpectedly, in this case, dehydrogenative addition of the B-H bond across the metal centre and the unsaturated ligand arm took place, with liberation of dihydrogen, resulting in formation of the dearomatized complex 28 in which the boryl group resides on the benzylic arm of the pincer complex.…”
Section: Boron-hydrogen Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaction of the dearomatized ruthenium pincer complex 27 (scheme 12) with pinacolor catechol borane, facile B-H bond cleavage occurred [31]. Unexpectedly, in this case, dehydrogenative addition of the B-H bond across the metal centre and the unsaturated ligand arm took place, with liberation of dihydrogen, resulting in formation of the dearomatized complex 28 in which the boryl group resides on the benzylic arm of the pincer complex.…”
Section: Boron-hydrogen Activationmentioning
confidence: 99%
“…This is then followed by H 2 elimination to yield the complex 28. Further insight regarding the dehydrogenative pathway was provided by a DFT study [31]. Based on this B-H activation mode, Ru-catalysed dehydrogenative coupling of boranes with arenes to form aryl boranes was demonstrated [31].…”
Section: Boron-hydrogen Activationmentioning
confidence: 99%
“…33 These reactions involve the X-H (X=H, C, O, N, and B) activations, [34][35][36][37][38][39][40][41] dehydrogenative coupling reactions, [42][43][44][45][46][47][48] and hydrogenation reactions. [49][50][51][52][53][54][55][56] In addition, a theoretical study about the ruthenium acridine complex was also reported.…”
Section: Computational Mechanistic Studiesmentioning
confidence: 99%
“…40 Cleavage of the B-H bond of boranes by the dearomatized ruthenium pincer complexes also involves metal-ligand cooperation. 41 The reaction favors the product where the Lewis acidic boron atom adds to the benzylic arm of the ligand and hydride adds to the ruthenium atom.…”
mentioning
confidence: 99%
“…Pyridine is aromatised because the inner ring C-C bond lengths are comparable to those observed in 1 at around 1.38 Å. 28 DFT calculations pointed towards an intermediate with aromatic pyridine and borane at the benzylic position, resembling the isolated complex 5. Interestingly, two π-π interactions are present in this structure between fluorinated rings and the central pyridine and one phenyl group (Fig.…”
Section: Reactivity Of 3 and 4 Featuring L* Ligandmentioning
confidence: 86%